Recovery of complete genomes and non-chromosomal replicons from activated sludge enrichment microbial communities with long read metagenome sequencing - Krithika Arumugam (Nature Portfolio, 2021)
Abstract New long read sequencing technologies offer huge potential for effective recovery of complete, closed genomes from complex microbial communities. Using long read data (ONT MinION) obtained from an ensemble of activated sludge enrichment bioreactors we recover 22 closed or complete genomes of community members, including several species known to play key functional roles in wastewater bioprocesses, specifically microbes known to exhibit the polyphosphate- and glycogen-accumulating organism phenotypes (namely Candidatus Accumulibacter and Dechloromonas, and Micropruina, Defluviicoccus and Candidatus Contendobacter, respectively), and filamentous bacteria (Thiothrix) associated with the formation and stability of activated sludge flocs. Additionally we demonstrate the recovery of close to 100 circularised plasmids, phages and small microbial genomes from these microbial communities using long read assembled sequence. We describe methods for validating long read assembled genomes using their counterpart short read metagenome-assembled genomes, and assess the influence of different correction procedures on genome quality and predicted gene quality. Our findings establish the feasibility of performing long read metagenome-assembled genome recovery for both chromosomal and non-chromosomal replicons, and demonstrate the value of parallel sampling of moderately complex enrichment communities to obtaining high quality reference genomes of key functional species relevant for wastewater bioprocesses.